Comparison of CD34+ cell enumeration between flow cytometric analysis and ADAMII-CD34 image-based fluorescence cell counter - Anchalee Thedsawad; Sirikwan Boonmoh; Orathai Taka; Weerapat Owattanapanich (PLoS ONE, 2026)
Background Accurate CD34 + cell enumeration is essential in stem cell transplantation. Flow cytometry (FC) is the standard method to determine optimal collection time of CD34 + stem cells harvesting for peripheral blood stem cell (PBSC) transplantation but is costly and requires skilled personnel. The ADAMII-CD34 cell counter may be a feasible alternative for PBSC apheresis samples and for cryopreserved stem cell products which are assessed by manual cell viability counting using the trypan blue exclusion method. Methods Fifty samples were analyzed (PBSC apheresis samples n = 25, cryopreserved stem cell products n = 25) from patients undergoing autologous PBSC transplantation or healthy donors. We assessed the quantitative agreement between methods. Results In the 25 PBSC apheresis samples, FC-based median viable CD34 + absolute count was 764.7 cells/µL (IQR 453.7–1532.5; range 60.5–3233.8). ADAMII-CD34 cell counter and FC showed almost perfect agreement [Lin’s concordance correlation coefficient (CCC) 0.99 (95% CI: 0.98 to 1.00), bias –0.46% (95% CI: –5.45 to 4.53), upper limit of agreement (LoA) 22.2% (95% CI: 13.5 to 30.8), and lower LoA –23.1% (95% CI: –31.7 to –14.4)]. For cryopreserved stem cell products, viable CD34 + cell dose (×10 6 cells/kg) measured by the ADAMII-CD34 cell counter and the estimated viable CD34 + cell dose (×10 6 cells/kg) determined by the trypan blue exclusion method showed poor agreement [Lin’s CCC 0.58 (95% CI: 0.31 to 0.76)]. Weighted Deming regression showed proportional bias [95% CI: slope 0.02 to 0.61]. Conclusions Quantitative agreement between the ADAMII-CD34 cell counter and FC for CD34 + enumeration in PBSC apheresis samples was acceptable within the analyzed range. It is user-friendly and more affordable than FC. However, ADAMII-CD34 and the trypan blue exclusion method of cryopreserved stem cell products showed a proportional bias. Further considerations are needed to optimize the process for cryopreserved stem cell products.